Pengaruh Kompetensi terhadap Peningkatan Kinerja Pegawai Distrik Sorong Utara - Suklu, Robianus; Sinay, Philipus; Pattiasina, Rendi Yudhistira (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the influence of competency on improving employee performance in the North Sorong District. The data analysis method used is quantitative descriptive analysis. significant testing via (t-test), using simple linear regression and determination coefficient (R2). The population in this study was all employees at the North Sorong District Office totaling 28 respondents and the sample was 28 respondents. Primary data was obtained through interviews, questionnaires and documentation studies.The results of the research variable reliability test show that competency has a Cronbach's alpha of 0.754, and employee performance has a Cronbach's alpha of 0.746, greater than 0.60. It was concluded that the three research variables were declared reliable and reliable. In the coefficient of determination test, an R square of 65.3% was obtained, meaning that competence influenced employee performance by 65.3%, while the remaining 34.7% was influenced by other factors not analyzed in this research. The results of the t test, where t count is 7,000 > from t table 1.7056, it can be said that the competency variable has a positive and significant effect on employee performance.